First isolation of aeromonas salmonicida subspecies salmonicida from diseased sea bass, dicentrarchus labrax (L.), cultured in Spain - Fernández Álvarez, Clara; Gijón, Daniel; Álvarez, Mireya; Santos Rodríguez, María Ysabel (Aquaculture Reports)
This work represents the first description of Aeromonas salmonicida subsp. salmonicida as causative agent of furunculosis in cultured sea bass, Dicentrarchus labrax (L.). Cumulative mortality in affected fish from two floating cages in the Mediterranean coast of Spain was 3.8%. Affected sea bass did not show the typical external signs of furunculosis in the first stages of the disease, however, when the disease progressed, open ulcers appeared on the skin and muscle. Internally, splenomegaly was the only pathological sign observed. Samples from diseased fish were subjected to standardized assays for pathogens screening. Negative results were obtained for parasites and fish viruses. A Gram-stain-negative rod-shaped bacterium was observed in smears from liver, kidney and spleen of all analysed fish. Pure bacterial cultures were recovered from liver, kidney and spleen of all diseased fish sampled during the two different outbreaks. Bacteriological, serological, molecular and chemotaxonomic analysis allowed the identification of the causative agent of sea bass mortalities as Aeromonas salmonicida subsp. salmonicida. The bacterial strains were susceptible to most of antimicrobial agents usually employed in aquaculture except to oxytetracycline. Pathogenicity assays demonstrated that the isolated bacteria were virulent for sea bass, turbot and rainbow trout SI